The Reversal Effect of Sigma-1 Receptor (S1R) Agonist, SA4503, on Atrial Fibrillation After Depression and Its Underlying Mechanism - Liu, Xin; Qu, Chuan; Shi, Shaobo; Ye, Tianxin; Wang, Linglin; Liu, Steven; Zhang, Cui; Liang, Jinjun; Hu, Dan; Yang, Bo (Frontiers in Physiology, 2019)
Aim Sigma-1 receptors have been investigated and shown to play a protective role in both depression and cardiovascular disease. SA4503, known as a σ1 receptor agonist, regulates cardiac calcium and potassium channels in rat models of depression. However, it remains unknown whether SA4503 can alleviate myocardial inflammation or conduction junctions in the atrium after exposure to chronic mild stress. Methods and Results Sprague-Dawley male rats received 28-day treatment with SA4503, simultaneously with chronic mild stress. Behavior measurements were assessed after the daily doses. Additionally, a multielectrode array assessment, electrophysiological study, immunohistochemistry analysis, histological analysis, and Western blot analysis were performed. Depression rats’ hearts showed abnormal electrical activity, including disordered excitation propagation and prolonged total activation time (TAT). In addition, atrial arrhythmias (AAs), induced by burst stimulation, showed higher incidence and longer duration in the depression group compared to the control group. These changes were related to reduced conduction junctions and enhanced spatial heterogeneity. Importantly, depressed rat hearts showed greater expression of inflammatory factors (TGF-α, IL-6, and TGF-β), more collagen distribution in the extracellular matrix, and lower expression of gap junction proteins (CX40 and CX43). Furthermore, SA4503 partially mitigated the above indices in the depression group (P < 0.01 for all groups). Conclusion These findings show the effects of the σ1R agonist SA4503; it alleviates atrial myocardial inflammation and conduction junctions after chronic mild stress. SA4503 may be the promising pharmacological agent to treat depression-related AAs by increasing conduction function, improving the expression of connexin 40 and 43, and reducing cardiac myocardial inflammation.